2001
DOI: 10.1054/bjoc.2000.1671
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime physical activity and breast cancer risk in the Shanghai Breast Cancer Study

Abstract: Frisch and colleagues (1985) reported that women who did not participate in collegiate athletics were at 1.86 times greater risk of breast cancer relative to collegiate athletes, 82% of whom were physically active in adolescence and 74% of whom maintained high physical activity levels into adulthood. Most subsequent studies have provided evidence for a reduced risk of breast cancer among women with high levels of physical activity (Friedenreich et al, 1998b). Inconsistencies in previous studies may be partly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
90
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 33 publications
8
90
2
3
Order By: Relevance
“…50 Changes in diet with an overall increase in dietary calories and a reduction in physical activity levels, particularly among urban residents (caused by the increased industrialization, life style and leisure activities transformation), 51 with a resulting in an increase in obesity, 52 have been shown to increase risk of breast cancer in China, as elsewhere. 53,54 Conclusions Population-based cancer incidence data are widely used in research 55 and in the decision-making process with respect to cancer control planning and evaluation by local or national authorities. This article shows that the cancers of high lethality that have been common in the Chinese population (stomach, liver, oesophagus) are showing some evidence of decline, at least in younger generations, but they remain major problems.…”
Section: Discussionmentioning
confidence: 99%
“…50 Changes in diet with an overall increase in dietary calories and a reduction in physical activity levels, particularly among urban residents (caused by the increased industrialization, life style and leisure activities transformation), 51 with a resulting in an increase in obesity, 52 have been shown to increase risk of breast cancer in China, as elsewhere. 53,54 Conclusions Population-based cancer incidence data are widely used in research 55 and in the decision-making process with respect to cancer control planning and evaluation by local or national authorities. This article shows that the cancers of high lethality that have been common in the Chinese population (stomach, liver, oesophagus) are showing some evidence of decline, at least in younger generations, but they remain major problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews concluded that physical activity both at young ages and in adulthood reduced the risk of breast cancer; IARC (2002) and Lagerros et al (2004). However, subsequent findings concerning premenopausal breast cancer are inconsistent, both for physical activity at young ages (Dorn et al, 2003;Steindorf et al, 2003;Yang et al, 2003;Margolis et al, 2005) and around diagnosis (AdamsCampbell et al, 2001;Gilliland et al, 2001;Matthews et al, 2001;Colditz et al, 2003;Dorn et al, 2003;Hirose et al, 2003;John et al, 2003;Steindorf et al, 2003;Yang et al, 2003;Margolis et al, 2005). Without evidence from a formal meta-analysis using individual data from all relevant studies, it is difficult to interpret the available results.…”
Section: Discussionmentioning
confidence: 99%
“…Although an expert group convened by the International Agency for Research on Cancer concluded that there was sufficient evidence that physical activity reduced the risk of premenopausal breast cancer (IARC, 2002), results from more recent studies have been contradictory (Adams-Campbell et al, 2001;Gilliland et al, 2001;Matthews et al, 2001;Colditz et al, 2003;Dorn et al, 2003;Hirose et al, 2003;John et al, 2003;Steindorf et al, 2003;Yang et al, 2003;Margolis et al, 2005).…”
mentioning
confidence: 99%
“…2 Nevertheless, epidemiologic data in studies on physical activity and breast cancer risk remain inconclusive. [3][4][5][6][7][8][9][10][11][12] Although some studies show a clear protection, 5,7,8,[12][13][14][15][16][17] others reveal only a weak, often nonsignificant association 18,19 or no association at all. 10,11,20,21 Many factors could explain these discrepancies.…”
mentioning
confidence: 99%